Occlusion - Thomson, Hamish (1975)
The investigation of the problems of occlusion is of immediate concern to every dental clinician. 'What would be the use of teeth, however beautiful, if they did not meet effectively?" This book presents a description and discussion of the tissues and functions of the masticatory system and of occlusion and articulation in particular. It describes methods of analysing occlusal problems and trans ferring occlusal records to articulators. A list of disturbances of occlusion is given and discussed and of the disorders which can result. These disorders include the mandibular dysfunction syndrome. Treatment methods include the part played by occlusion in routine restorative and pros thodontic procedures, occlusal adjustment of the natural teeth, and the treatment of disorders of occlusion.